2008
DOI: 10.1063/1.2974084
|View full text |Cite
|
Sign up to set email alerts
|

Thickness dependence of space charge limited current and injection limited current in organic molecular semiconductors

Abstract: We report the experimental investigations on space charge limited current (SCLC) and injection limited current (ILC) in copper phthalocyanine (CuPc), sandwiched between two metal electrodes. Thickness dependence of current-voltage characteristics of SCLC and ILC is accurately reproduced by the electric field and temperature dependent charge carrier mobility, without invoking charge density dependent mobility. These results are interpreted using a consistent description of SCLC and ILC, based on a unified model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 18 publications
2
24
0
Order By: Relevance
“…Because, it has been shown that if the barrier at metal/organic interface is more than 0.3 eV, current transport is due to injection limited current, where the electric field is nearly uniform, and traps effects in organic layers are not important [14]. Also, for PbSe QDs we find the energy levels well aligned inside the organic materials used (see Fig.…”
mentioning
confidence: 70%
“…Because, it has been shown that if the barrier at metal/organic interface is more than 0.3 eV, current transport is due to injection limited current, where the electric field is nearly uniform, and traps effects in organic layers are not important [14]. Also, for PbSe QDs we find the energy levels well aligned inside the organic materials used (see Fig.…”
mentioning
confidence: 70%
“…4(b) shows the J-V characteristics of ITO/CuPc/Au based two terminal devices in which CuPc thin lms were grown at T G ¼ 120 C. Initially, the current increases linearly in this device, but as the bias increases, injected carrier density exceeds the intrinsic free carrier density and current follows SCLC. 34,35 SCLC is observed when there is either no or very low density of traps. In SCLC regime, slope starts from 2 and eventually increases with bias due to the eld dependent carrier mobility m(F,T), given by 36…”
Section: Arrangement Of Molecules In Cupc Thin Filmsmentioning
confidence: 99%
“…,T]F(x) simultaneously. 34 Upper inset of Fig. 4(b) shows the TSCAP measurements of the corresponding device.…”
Section: Arrangement Of Molecules In Cupc Thin Filmsmentioning
confidence: 99%
“…Agrawal et al [23] compared injection-limited currents and SCL currents in a copper-phthalocyanine sandwich cell with ITO and Al electrodes. An analysis of experimental data yields consistent values for the width of the DOS distribution as well as for inter-site separation.…”
Section: Box 33 Arrhenius Plotmentioning
confidence: 99%